The Definition and the Development of the Religious Protectorate of France in the Ottoman Lands - Buğra Poyraz (Eskişehir Osmangazi Üniversitesi İlahiyat Fakültesi Dergisi)
The aim of this study is to emphasize the position of France as the Protector of Catholics living on the lands of the Ottoman Empire, starting with Latin Catholics, and the development of this position, in accordance with the articles of capitulations given to this country. France was able to maintain its influence in the region by acting as the Protector of the Eastern Catholics, holding this prestigious and priority title among other European powers, giving the impression of establishing a visible alliance with the Papacy; and through this, the ambassadors of France had ceremonial and honorary privileges in the capital of the Ottoman Empire. With the religious Protectorate of France in the East, the issue of Eastern Christians emerged for the first time, and these communities became a tool to increase France's influence in the East. France represented not only Catholic clergy, but also the Catholic institutions such as schools, hospitals, orphanages and lay people before the Ottoman administration and solved the legal problems between them. Although France tried to extend its protection from Catholics to all Christians, this was not accepted by the Ottoman administration. As a matter of fact, the existence of the Greek and Armenian communities, which were the components of the Ottoman Millet System, made this request of France impossible.